2018
DOI: 10.1007/s00253-018-9229-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota assemblages of water, sediment, and intestine and their associations with environmental factors and shrimp physiological health

Abstract: Microorganisms play crucial roles in nutrient cycling, water quality maintenance, and farmed animal health. Increasing evidences have revealed a close association between unstable microbial environments and disease occurrences in aquaculture. Thereupon, we used high-throughput sequencing technology to comprehensively compare the bacterial communities of water, sediment, and intestine in mariculture ponds at the middle and late stages of Litopenaeus vannamei farming and analyzed whether changes of their microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 50 publications
6
78
3
Order By: Relevance
“…The intestine microbiota of shrimp is increasingly recognized to facilitate host health, and its influencing factors have been extensively studied. To the best of our knowledge, the intestine microbiota of shrimp is not only affected by biotic factors (Burns et al, 2016;Dai et al, 2017;Zeng et al, 2017) but also by abiotic factors (e.g., salinity and temperature) (Zhang et al, 2016;Huang et al, 2018). Our study reinforced the evidence that the shrimp intestine bacterial communities are influenced by the salinity of rearing water, with marked variations observed of FIGURE 6 | Ecological process analyses on shrimp intestine bacterial assembly in the LS and HS groups.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The intestine microbiota of shrimp is increasingly recognized to facilitate host health, and its influencing factors have been extensively studied. To the best of our knowledge, the intestine microbiota of shrimp is not only affected by biotic factors (Burns et al, 2016;Dai et al, 2017;Zeng et al, 2017) but also by abiotic factors (e.g., salinity and temperature) (Zhang et al, 2016;Huang et al, 2018). Our study reinforced the evidence that the shrimp intestine bacterial communities are influenced by the salinity of rearing water, with marked variations observed of FIGURE 6 | Ecological process analyses on shrimp intestine bacterial assembly in the LS and HS groups.…”
Section: Discussionsupporting
confidence: 81%
“…So far, research into the effects of abiotic factors on the intestine microbiota of aquatic animals has just begun. Some studies have shown that the intestine microbiota of aquatic animals is significantly affected by the salinity, ammonia, and temperature of rearing water (Sullam et al, 2012;Cornejo-Granados et al, 2018;Huang et al, 2018). Aquatic animals live in the water habitat with environmental conditions (e.g., salinity, temperature) are constantly experience changes, and whether these abiotic factors can influence on host intestine microbiota, causing further adverse effects on host health status, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Alphaproteobacteria (such as Rhodobacterales and Rhizobiales) and Planctomycetales are associated with healthy shrimp Xiong et al, 2017) and are less abundant in diseased (Zhu et al, 2016;Xiong et al, 2017) or significantly less in slow growth ones (p < 0.01) . As beneficial bacteria, Rhodobacteraceae have been applied in shrimp aquaculture for their abilities to degrade organic compounds in ponds (Huang F. et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similar microbial community composition was detected between water, sediment and animal gut microbiota [15,16]. Hence, the water and sediment microbiota may serve as a source of the gut microbiota of farmed animals, which influences animal health and growth performance [17,18].…”
Section: Introductionmentioning
confidence: 61%